Neuropeptide Y as a risk factor for cardiorenal disease and cognitive dysfunction in chronic kidney disease: translational opportunities and challenges. (9th December 2021) - Zoccali, Carmine; Ortiz, Alberto; Blumbyte, Inga Arune; Rudolf, Sarina; Beck-Sickinger, Annette G; Malyszko, Jolanta; Spasovski, Goce; Carriazo, Sol; Viggiano, Davide; Kurganaite, Justina; Sarkeviciene, Vaiva; Rastenyte, Daiva; et al.
ABSTRACT: Neuropeptide Y (NPY) is a 36-amino-acid peptide member of a family also including peptide YY and pancreatic polypeptide, which are all ligands to Gi/Go coupled receptors. NPY regulates several fundamental biologic functions including appetite/satiety, sex and reproduction, learning and memory, cardiovascular and renal function and immune functions. The mesenteric circulation is a major source of NPY in the blood in man and this peptide is considered a key regulator of gut–brain cross talk. A progressive increase in circulating NPY accompanies the progression of chronic kidney disease (CKD) toward kidney failure and NPY robustly predicts cardiovascular events in this population. Furthermore, NPY is suspected as a possible player in accelerated cognitive function decline and dementia in patients with CKD and in dialysis patients. In theory, interfering with the NPY system has relevant potential for the treatment of diverse diseases from cardiovascular and renal diseases to diseases of the central nervous system. Pharmaceutical formulations for effective drug delivery and cost, as well as the complexity of diseases potentially addressable by NPY/NPY antagonists, have been a problem until now. This in part explains the slow progress of knowledge about the NPY system in the clinical arena. There is now renewed research interest in the NPY system in psychopharmacology and in pharmacology in general and new studies and a new breed of clinical trials may eventually bring the expected benefits in human health with drugs interfering with this system.